2020
DOI: 10.1111/aas.13709
|View full text |Cite
|
Sign up to set email alerts
|

Consensus on predictors of clinical deterioration in emergency departments: A Delphi process study

Abstract: Clinical deterioration in hospitalised patients is often preceded by deterioration in physiological parameters. 1 In 1997, Morgan et al 2 proposed the first early warning score (EWS) system to alert clinicians to deteriorating patients using an aggregated, weighted score of vital signs. Early warning scores generally have a track (abnormal vital signs) and a trigger (predetermined calling or response criteria). 3 The predetermined calling or responses of the EWS often consist of increased observation, alerts t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
3

Relationship

2
1

Authors

Journals

citations
Cited by 3 publications
(4 citation statements)
references
References 62 publications
0
4
0
Order By: Relevance
“…The study was designed to investigate whether a new SA model adding additional parameters and team risk assessments to the conventional regional EWS could reduce the proportion of CD through earlier identification of the deteriorating patient. As aforementioned, the vital signs, skin observations, dyspnea, pain, and relatives concerns were based on the results of a modified Delphi technique identifying potentially relevant and applicable predictors of CD in an adult ED population 20 ; whereas, clinical concern and patients’ concern were inspired by the Cincinnati SA model 17 . Studies in other settings have found that adding subjective parameters to EWS may lead to improved patient outcomes (eg, decrease in ICU admissions and identifying the deteriorating patient before triggering the EWS system) 17,26‐28 .…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…The study was designed to investigate whether a new SA model adding additional parameters and team risk assessments to the conventional regional EWS could reduce the proportion of CD through earlier identification of the deteriorating patient. As aforementioned, the vital signs, skin observations, dyspnea, pain, and relatives concerns were based on the results of a modified Delphi technique identifying potentially relevant and applicable predictors of CD in an adult ED population 20 ; whereas, clinical concern and patients’ concern were inspired by the Cincinnati SA model 17 . Studies in other settings have found that adding subjective parameters to EWS may lead to improved patient outcomes (eg, decrease in ICU admissions and identifying the deteriorating patient before triggering the EWS system) 17,26‐28 .…”
Section: Discussionmentioning
confidence: 99%
“…The vital signs comprising the regional EWS system, skin observations, dyspnea, pain, and relatives concerns were based on the results of a modified Delphi technique identifying potentially relevant and applicable predictors of CD in an adult ED population, 20 whereas clinical concern and patients’ concern were inspired by the Cincinnati SA model 17 …”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…IQR and median were calculated for each patient case. A consensus for inclusion was defined by a median score and IQR of 7–9; for exclusion, a consensus was defined by a median score and IQR of 1–3 17 19 20. Non-consensus was defined as all other scores yielding reassessment in round 2, for example, a score and IQR falling within the 4–6 range or an IQR crossing the 4–6 range.…”
Section: Methodsmentioning
confidence: 99%